Investigation into the Flow Properties of Coarse Solid Fuels for Use in Industrial Feed Systems. (27th May 2015) - Craven, James M.; Swithenbank, Jim; Sharifi, Vida N.
Abstract : Material feeding and handling systems have been cited as one of the most common causes of process downtime where thermochemical conversion processes are concerned. New and emerging fuels come in a variety of forms, and if such fuels are to be deployed widely it is imperative that material feeding and handling systems are designed appropriately. This study proposes an approach for designing material feeding and handling systems for use with coarse solid fuels. The data obtained from this study indicates particle size to be one of the key issues affecting the flowability of bulk solids further to the uniformity in particle shape. Coarse bulk solid samples were shown to flow more freely than their milled and pulverised counterparts, generating higher degrees of flowability. The results from this study were also applied to a new feed system used for feeding solid fuels to high pressure processes named the Hydraulic Lock Hopper. In this study the Hydraulic Lock Hopper demonstrated the feeding of wood pellets, torrefied spruce pellets, and ground anthracite coal grains against a pressure of 25 barg in two modes of operation. Energy savings compared to conventional lock hopper systems were recorded in the region of 80%.